Leveraging a luxury fashion brand through social media - Romão, Maria Teresa (2018)
Romão, M. T., Moro, S., Rita, P., & Ramos, P. (2019). Leveraging a luxury fashion brand through social media. European Research on Management and Business Economics, 25(1), 15-22. DOI: 10.1016/j.iedeen.2018.10.002